2010
DOI: 10.1177/0969733009355380
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of problem-based learning and conventional teaching in nursing ethics education

Abstract: The aim of this study was to compare the learning effectiveness of peer tutored problem-based learning and conventional teaching of nursing ethics in Taiwan. The study adopted an experimental design. The peer tutored problem-based learning method was applied to an experimental group and the conventional teaching method to a control group. The study sample consisted of 142 senior nursing students who were randomly assigned to the two groups. All the students were tested for their nursing ethical discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
124
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 18 publications
10
124
0
7
Order By: Relevance
“…This finding falls in line with the study of Lin et al (2010), they found that there were significant differences in satisfaction with self-motivated learning and critical thinking among the groups. [33] In addition, this finding is also in conformity with the results of another study done by Stone et al (2013), the study had concluded that nursing students could benefit from peer learning, with an increment in confidence and competence and a decline in anxiety.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding falls in line with the study of Lin et al (2010), they found that there were significant differences in satisfaction with self-motivated learning and critical thinking among the groups. [33] In addition, this finding is also in conformity with the results of another study done by Stone et al (2013), the study had concluded that nursing students could benefit from peer learning, with an increment in confidence and competence and a decline in anxiety.…”
Section: Discussionsupporting
confidence: 82%
“…[33] In addition, this finding is also in conformity with the results of another study done by Stone et al (2013), the study had concluded that nursing students could benefit from peer learning, with an increment in confidence and competence and a decline in anxiety. [34] Moreover, the present study's result is also consistent with the findings of Andreesen et al (2014), they found that the intervention group stressed on the role of the tutors as competent and well-trained teachers.…”
Section: Discussionsupporting
confidence: 79%
“…[14,15] Thus, it has been suggested that nursing students could learn to develop desirable relationships with other nurses, nursing clients as humans, and various cooperators as a result of ethics education, as well as to understand their professional obligations as experts and to establish desirable professional values. Although there have been some preceding studies [13,16,17] measuring the influence of ethics education, few have measured the influence of ethics education based on the extent of change in awareness regarding the code of ethics. Changes in nursing students' awareness regarding the ethics code can increase application in practice.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated evidence of learning effectiveness for both groups, however, the PBL group was found to be more effective. Students who participated in PBL reported higher satisfaction with skills in self-motivation and critical thinking when compared to the group who participated in conventional teaching (Lin et al, 2010). The researchers also found that the distance between the students' developmental level and their potential was supported by engaging in a socially interactive process of problem solving that was influenced by the skills and abilities of each student.…”
Section: Disaster Nursingmentioning
confidence: 66%
“…In an experimental study which compared PBL and conventional teaching in an undergraduate nursing program, Lin, Lu, Chung, and Yang (2010) identified PBL as an organized, student-centered educational strategy. The results demonstrated evidence of learning effectiveness for both groups, however, the PBL group was found to be more effective.…”
Section: Disaster Nursingmentioning
confidence: 99%